2022
DOI: 10.3390/diagnostics12112655
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-to-Monocyte Ratio and Clinical Outcomes in Cholangiocarcinoma: A Systematic Review and Meta-Analysis

Abstract: Lymphocyte-to-Monocyte ratio (LMR) has shown an association with survival outcomes in several oncological diseases. This study aimed to evaluate the association between LMR and clinical outcomes for cholangiocarcinoma patients. A systematic review and meta-analysis were performed to assess the association between LMR values and overall survival (OS), disease-free survival (DFS), recurrence-free survival (RFS) and time to recurrence (TTR) in cholangiocarcinoma patients. We used Hazard ratio (HR) and their 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Gao and colleagues revealed that a low LMR was associated with poor OS and reduced DFS/PFS in nasopharyngeal carcinoma through a meta-analysis involving 3773 patients [ 46 ]. Dotto-Vasquez et al performed a meta-analysis including 19 studies and indicated that cholangiocarcinoma patients with low values of LMR were associated with worse OS and poor time to recurrence (TTR) [ 47 ]. In a recent meta-analysis comprising 8361 cases, it was reported that decreased pretreatment LMR was significantly correlated with reduced PFS and worse OS in lung cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gao and colleagues revealed that a low LMR was associated with poor OS and reduced DFS/PFS in nasopharyngeal carcinoma through a meta-analysis involving 3773 patients [ 46 ]. Dotto-Vasquez et al performed a meta-analysis including 19 studies and indicated that cholangiocarcinoma patients with low values of LMR were associated with worse OS and poor time to recurrence (TTR) [ 47 ]. In a recent meta-analysis comprising 8361 cases, it was reported that decreased pretreatment LMR was significantly correlated with reduced PFS and worse OS in lung cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the progression of malignancy, it influences the cellular components of the immune system, and its chronic state stimulates immunity and is associated with a poor prognosis [28,29]. In this sense, several studies have demonstrated the importance of some inflammatory markers in the prognosis of cancer patients, such as the lymphocyte/monocyte ratio, which is a prognostic indicator in head and neck cancer [30], rectal cancer [31], ovarian cancer [32] and cholangiocarcinoma [33]. We also have the NLR, which is a prognostic indicator in melanoma [34], endometrial cancer [35], or solid tumors [36].…”
Section: Discussionmentioning
confidence: 99%